FLUXOFENIM USED AS A SAFENER ON SORGHUM SEED FOR S-METOLACHLOR HERBICIDE - Vaz da Silva, Joao Renato; Martins, Cibele Chalita [UNESP]; Silva Junior, Antonio Carlos da [UNESP]; Martins, Dagoberto [UNESP] (Univ Federal Uberlandia, 2014)
This study aimed to evaluate the efficiency of protective fluxofenim seed treatment of sorghum hybrids DKB510 and SCG340, in order to increase the selectivity to the herbicide S-metolachlor applied pre-emergence and to determine the activity of detoxification enzyme glutathione S-transferase (GST). This work was divided into two stages. The first step consisted of field evaluation of the effectiveness of the shield to reduce visual symptoms of plant injury caused by the herbicide and the second determined the activity of GST. It was compared the susceptibility of sorghum seeds to the herbicide by means of visual assessment of injuries at 3, 7, 15 and 30 days after emergence (DAE), root dry weight and shoot at 10 DAE, and determination of activity GST. The treatments were: application of the safener dose at 0 and 40 mL per 100 kg of seed, and spraying of the herbicide S-metolachlor at rates of 1,440 and 2,880 g a.i. ha(-1), and a control without herbicide. The safener use to seed treatment for both sorghum hybrids (DKB510 and SCG340) increased tolerance to the herbicide S-metolachlor in two doses, and the best results were obtained at a dose of 1,440 g ha(-1). The GST enzyme activity showed an increase when using the fluxofenim prior to application of the herbicide S-metolachlor at a dose of 1,440 g ha(-1) for the two hybrids.
Keywords: Herbicide; Detoxification; Selectivity; Sorghum bicolor; S-tranferase